2019
DOI: 10.1038/s41598-019-51513-1
|View full text |Cite
|
Sign up to set email alerts
|

Impact of UV sterilization and short term storage on the in vitro release kinetics and bioactivity of biomolecules from electrospun scaffolds

Abstract: To effectively translate bioactive scaffolds into a preclinical setting, proper sterilization techniques and storage conditions need to be carefully considered, as the chosen sterilization technique and storage condition might affect the structural and mechanical properties of the scaffolds, as well as the bioactivity and release kinetics of the incorporated biomolecules. Since rarely tested or quantified, we show here in a proof-of-concept study how these parameters are affected by UV sterilization and one we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 42 publications
1
10
0
Order By: Relevance
“…However, a major challenge is to preserve the bioactivity, which is important in maintaining cell attachment and behaviour [14,15]. Also additional characteristics can be inadvertently effected by washing and sterilization steps which could cause damage or removal [16,17]. Alternatively, controlled inclusion of protein into polymer fibres can lead to increased stabilisation and function.…”
Section: Introductionmentioning
confidence: 99%
“…However, a major challenge is to preserve the bioactivity, which is important in maintaining cell attachment and behaviour [14,15]. Also additional characteristics can be inadvertently effected by washing and sterilization steps which could cause damage or removal [16,17]. Alternatively, controlled inclusion of protein into polymer fibres can lead to increased stabilisation and function.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, there are some factors that have been ignored that could affect the release kinetics and bioactivity of drugs or biomolecules at the clinical use. Evrova et al presented a proof-of-concept study of how the sterilization process and period of storage can affect the properties of bioactivity and releases kinetics of a growth factor incorporated in an electrospun polyester urethane block copolymer called DegraPol (DP), it was found that during the storage and UV sterilization there was no visible impact in the morphology and physicochemical properties but UV sterilization affects the release in platelet-derived growth factor significantly, and the release kinetics decreased until 85% [119]. There is not doubt, electrospinning is still a promising technique for DDS and researchers will continue exploring different systems to overcome the limitations until now.…”
Section: Discussionmentioning
confidence: 99%
“…Simultaneously, tissue engineering applies the principles of material engineering and the life sciences to manufacture functional tissue material to replace diseased or damaged organs and restore the functionality of these organs without having to subsequently remove them [101][102][103][104][105][106][107][108]. Electrospinning can be employed to create porous three-dimensional structures to which cells can adhere, proliferate, grow, and differentiate in order to repair and replace damaged tissue [109][110][111].…”
Section: Recent Biological and Medical Engineering Applicationsmentioning
confidence: 99%